Structural evolution in ZrNxOy thin films as a function of temperature - Cunha, L. (2006)
Single-layered zirconium oxynitride (ZrNxOy) thin films have been deposited on steel substrates, at a constant temperature of 300 °C, by radiofrequency (rf) reactive magnetron sputtering of a pure Zr target in an argon-oxygen-nitrogen atmosphere. The variation of the flow rate of the reactive gases enabled changes in the composition and structure of the films. X-ray diffraction (XRD) and glancing incidence X-ray diffraction (GIXRD) were used to study the as-deposited films and their structural changes during or after heat treatment, from 400 to 900 °C, in controlled atmosphere and in vacuum.